Pengaruh Ketangkasan Organisasi Untuk Mencapai Kesuksesan Digital Transformasi - Octavia Octavia; Denie Amanda; Alamsjah Alamsjah; Firdaus Firdaus (Syntax Idea)
The rapid development of digital technology and its application throughout business organizations makes digital transformation a source of sustainable business dynamics. Previous research has investigated several factors that influence digital transformation, but there is little research on the impact of organizational agility on digital transformation in organizations. To fill this gap, this research aims to investigate how organizational agility and the factors that influence organizational agility influence the success of digital transformation in companies. A survey study was conducted to empirically test the model. Data was collected from 158 private and BUMN employees in Indonesia. The findings show that organizational agility has a significant effect on digital transformation and the speed of response to market demands is an important predictor of organizational agility.